Toroidal metasurfaces in a 2D flatland - Gupta, Manoj (2020)
A toroidal dipole is a new class of electromagnetic excitations and are different from traditional electric and magnetic dipoles. Toroidal dipoles are described by the poloidal currents flowing on the surface of torus and have opened a new route to control radiative losses via near field coupling mechanism or radiation cancellation approach in the unit cell of metasurface. Radiative loss engineering in metamaterials is one of the most fundamental requirements to gauge the suitability of a metaphotonic device for a specific on-demand application. Here, we discuss strategies to excite toroidal dipolar modes in a planar metasurface which were initially thought to exist only in three-dimensional (3D) arrangements. Two dimensional (2D) toroidal metasurfaces are conceptual simplification of 3D toroid configurations, which pose fabrication challenges at micro-nanoscales. We further discuss the destructive interference between electric and toroidal dipoles to realize non-radiating modes in the form of an anapole excitation that fulfills the requirement for the excitation of extremely large quality factor resonances. Overall, the intriguing features of a toroidal dipole could have significant implications on the design of resonant metamaterials that are important for the development of low-loss sensors, modulators, filters, and efficient cavities for strong light matter interactions.